SOCIO-CULTURAL PRACTICES LEADING TO CHILD DEATH IN ANICENT ROME AND IBADAN (2012)
In ancient Rome and modern Ibadan, certain socio-cultural behavior exhibited by the people tended to highlight the thought pattern of the social and behavioural attitudes of the people. These behavaiour hampered heath and other issues in the socio-cultural behavioral attitude/practices that probably led to child death. The paper adopts a methodology that is both historical and comparative highlight these factors. Sources utilized on ancient Rome were the work s of classical and contemporary authors. For modern Ibadan, information was gathered from medical literature and newswpaper reports. The data were sudjected to content analysis. This paper discovered that some social cultural practices such as child exposure and abandonment. Religious/superstitious beliefs and social deprivation caused child death in both societies.The paper concludes with the ideology that effective reorientation and propaganda are needful in Ibadan as these would help curb preventable child death